Contrast-Induced Nephropathy: What We Know, What We Think We Know, and What We Don't Know - Funaki, Brian (Thieme Medical Publishers, 2005)
Contrast-induced nephropathy is a common but poorly understood problem. A large body of literature devoted to the subject is replete with contradictions and conflicting reports. The purpose of this article is to summarize our current understanding of the problem by reviewing some of the best studies done to date. Recommendations based on the current literature are also provided.